A role for PACE4 in osteoarthritis pain: evidence from human genetic association and null mutant phenotype. Issue 6 (22nd March 2012) - Malfait, Anne-Marie; Seymour, Albert B; Gao, Feng; Tortorella, Micky D; Le Graverand-Gastineau, Marie-Pierre Hellio; Wood, Linda S; Doherty, Michael; Doherty, Sally; Zhang, Weiya; Arden, Nigel K; Vaughn, Frances L; Leaverton, Paul E; et al.
Abstract : Objectives: The aim of this study was to assess if genetic variation in the PACE4 (paired amino acid converting enzyme 4) gene Pcsk6 influences the risk for symptomatic knee osteoarthritis (OA). Methods: Ten PCSK6 single nucleotide polymorphisms were tested for association in a discovery cohort of radiographic knee OA (n=156 asymptomatic and 600 symptomatic cases). Meta-analysis of the minor allele at rs900414 was performed in three additional independent cohorts (total n=674 asymptomatic and 2068 symptomatic). Pcsk6 knockout mice and wild-type C57BL/6 mice were compared in a battery of algesiometric assays, including hypersensitivity in response to intraplantar substance P, pain behaviours in response to intrathecal substance P and pain behaviour in the abdominal constriction test. Results: In the discovery cohort of radiographic knee OA, an intronic single nucleotide polymorphism at rs900414 was significantly associated with symptomatic OA. Replication in three additional cohorts confirmed that the minor allele at rs900414 was consistently increased among asymptomatic compared to symptomatic radiographic knee OA cases in all four cohorts. A fixed-effects meta-analysis yielded an OR=1.35 (95% CI 1.17 to 1.56; p=4.3×10 −5 and no significant between-study heterogeneity). Studies in mice revealed that Pcsk6 knockout mice were significantly protected against pain in a battery of algesiometric assays. Conclusions: These results suggest that a variant in PCSK6 is strongly associated with protection against pain in knee OA, offering some insight as to why, in the presence of the same structural damage, some individuals develop chronic pain and others are protected. Studies in Pcsk6 null mutant mice further implicate PACE4 in pain.